Isolation and identification fungi from spoilage fruits and vegetables and study ability of it to produce enzymes lyase of cell wall - Hiba Taha (Mesopotamia Journal of Agriculture)
The objective of this study was to isolate a potential fungi and characterize it from  local markets fruits and vegetables during the period between October 2013 to March 2014 , 22 fungal strains were isolated as follow Alternaria alternata , three species of Aspergillus sp. Cephalosporium sp. ، Cladosporium sp., Colletotrichum sp., Curvularia lunata , Epicoccum sp., two species of Fusarium spp., Geotrichum sp., Macrophomina phaseolina , Penicillium sp., Pythium sp., Rhizoctonia solani, Rhizopus stolonifer, Stemphylium  sp., Trichoderma  harzianum and Trichothecium sp. . A.alternata and  Penicillium sp. were  most frequents during October ,November, December and January while Penicillium was most frequents during February and March. Observations showed that fungal species were significantly differed for their ability to produse Pectinase , Cellulase and Amylase . Curvularia lunata , Fusarium sp., Penicillium sp.,  Rhizoctonia solani , Stemphylium, were produced the three enzymes while Fusarium oxysporum, Macrophomina phaseolina  and Colletorichum sp., produced both Pectinase and Cellulase , Cladosporium sp., was predicted to be not produce  of the three enzymes Macrophomina  phaseolina  predicted to be fungus to record  highest activity for Pectinase test , low activity was recorded for Pectinase test with Alternaria alternata all isolated fungi showed positive response to Cellulase with one exeption  Cladosporium sp., highest activity for cellulase by Fusarium solani . Rhizoctonia solani recorded highest activity for amylase while Stemphylium sp. was the lowest.